BALANCED SCORECARD DALAM PENGUKURAN DAN OPTIMALISASI KINERJA DI UNIVERSITAS X: PENDEKATAN ANALITIS - aksan, ismul; Sinen, Kasim; Kusumaningrum, Sheila; Mahu, Rusna (JURNAL MANAJEMEN DAKWAH, 2024)
This study aims to evaluate the performance of University X using a Balanced Scorecard (BSC) framework adapted to the context of higher education in Indonesia, such as measurements covering service inclusiveness, locally-based academic innovation, and university funding sustainability. A total of 230 participants were selected, consisting of 99 educators, 44 administrative staff, and 87 students. Data were collected through questionnaires, documentation, and literature studies with random sampling techniques to obtain respondents. The study used quantitative methods, analyzing both financial and non-financial metrics. The results of data analysis show the following performance results: (1) The financial perspective shows consistent improvement, with financial performance rated as economical, highly effective, and increasingly efficient throughout 2021 to 2023. (2) The customer perspective shows a high level of satisfaction in all dimensions, with powerful results in the reliability and assurance dimensions. (3) The internal business process perspective reflects good operational efficiency, and (4) the learning and growth perspective shows excellent results in capacity building and institutional development. This research provides a comprehensive assessment of the performance of University X, as well as offers insights for future strategic improvements in higher education institutions.